Kinetic studies of rubidium extraction from muscovite using chlorination roasting-water leaching process - CHEN Li-jie; HUANG Lin-qing; YUAN Lu-cheng; TIAN Lei (工程科学学报, 2018)
Rubidium is a very active and highly dispersed rare alkali metal, which has a wide range of applications in space technology, electronics, bioengineering, and materials science. To date, no single mineral with the industrial exploitation of rubidium has been found. Rubidium is mainly associated with cesium lithium mica, pollucite, carnallite, potash, seawater, and salt lake brine. In recent years, a large amount of rubidium muscovite has been found in China, and they have become an important resource for extracting rubidium. If comprehensively explored, they will alleviate the shortage of rubidium resources in China. Therefore, it is imperative to develop a simple and highly efficient process for rubidium muscovite exploration. Here, a chlorination roasting process was proposed to recover rubidium from the distinctive rubidium-containing muscovite. According to the differential thermal analysis and thermogravimetric analysis (DTA-TG) curves of chlorinated roasting, the temperature of the chlorination reaction using calcium chloride is about 100℃ lower than that of sodium chloride, and the chlorination is more efficient with CaCl2 than NaCl. Subsequently, the impact of chlorination temperature on the rubidium extraction rate was investigated. The results show that the rubidium can be chlorinated only when the chlorination temperature reaches 800℃, whereby the rubidium extraction rate is 96.71%. The rubidium chlorination rate largely increases with, especially after 800℃; this shows that the high temperature is beneficial to the chlorination roasting of rubidium. Finally, the kinetics results of the chlorination roasting of the kaolin ore show that the extraction rate of rubidium is controlled by the chemical reaction, and the activation energy in the roasting temperature range is 42.22 kJ·mol-1.